Zinc Fractions and Their Relationship with Soil Properties in Rice Growing Soils of South Kashmir - M.H. Chesti (Journal of the Indian Society of Soil Science, 2022)
A study was carried out during 2020-2021, to quantify different fractions of zinc (Zn) in rice growing soils of Kashmir valley. The area delineated for study was Anantnag and Kulgam districts located in South of Kashmir valley, owing to the fact that rice is the staple food of the valley grown on a large scale in this region. Ninety surface soil samples (0-25 cm), forty five from each district were collected and analyzed for various Zn fractions and soil properties. The sequential extraction scheme was used to fractionate Zn into water soluble-Zn, exchangeable-Zn, organically complexed-Zn, amorphous sesquioxide bound-Zn, crystalline sesquioxide bound-Zn and residual-Zn. The total-Zn was calculated as the sum of all the fractions which varied from 58.9 to 65.6 and 56.4 to 58.2 mg kg-1, respectively for the districts Anantnag and Kulgam. The labile fractions such as water soluble (1%) and exchangeable Zn (2-3%) contributed very little to total-Zn, whereas residual-Zn was the most dominant fraction, accounting for 69 to 72% of total- Zn. Among the physicochemical properties, soil pH and organic carbon were the key factors that governed the distribution of Zn in different chemical pools in both the districts.